Analisis Semiotika Roland Barthes pada Iklan Good Day Coffee Versi “Rizky Febian & Tiara Andini” - Al Gadri, Henri Henriyan (Universitas Mathla'ul Anwar Banten, 2022)
This study discusses the semiotic analysis of Roland Barthes' theory which includes three dimensions, namely Denotation, Connotation and Myth (myth). The purpose of this study was to determine the meaning of denotation, connotation and myths in the Good Day Coffee advertisement. The research results obtained by Good Day Coffee version